Qualitative rather than quantitative changes are hallmarks of fibroblasts in bleomycin-induced pulmonary fibrosis - Tsukui, Tatsuya; Ueha, Satoshi; Abe, Jun; Hashimoto, Shin-ichi; Shichino, Shigeyuki; Shimaoka, Takeshi; Shand, Francis H W; Arakawa, Yasuka; Oshima, Kenshiro; Hattori, Masahira; Inagaki, Yutaka; Tomura, Michio; et al. (The American journal of pathology, 2013)
Pulmonary fibrosis is characterized by accumulation of activated fibroblasts that produce excessive amounts of extracellular matrix components such as collagen type I. However, the dynamics and activation signatures of fibroblasts during fibrogenesis remain poorly understood, especially in vivo. We examined changes in lung tissue cell populations and in the phenotype of activated fibroblasts after acute injury in a model of bleomycin-induced pulmonary fibrosis. Despite clustering of collagen type I-producing fibroblasts in fibrotic regions, flow cytometry-based quantitative analysis of whole lungs revealed that the number of fibroblasts in the lungs remained constant. At the peak of inflammation, fibroblast proliferation and apoptosis were both increased, suggesting that the clustering was not merely a result of proliferation, but also of fibroblast migration from nearby alveolar walls. Parabiosis experiments demonstrated that fibroblasts were not supplied from the circulation. Comprehensive gene expression analysis of freshly isolated fibroblasts revealed a detailed activation signature associated with fibrogenesis, including changes in genes responsible for migration and extracellular matrix construction. The Spp1 gene, which encodes osteopontin, was highly up-regulated and was an identifying characteristic of activated fibroblasts present at the sites of remodeling. Osteopontin may serve as a useful marker of profibrotic fibroblasts. These results provide insights into the cellular and molecular mechanisms underlying pulmonary fibrosis and provide a foundation for development of specific antifibrotic therapies.